Verifying Feighner’s Hypothesis; Anorexia Nervosa Is Not a Psychiatric Disorder - Södersten, Per; Brodin, Ulf; Zandian, Modjtaba; Bergh, Cecilia E. K. (Frontiers in Psychology, 2019)
Mental causation takes explanatory priority over evolutionary biology in most accounts of eating disorders. But the evolutionary threat of starvation has produced a brain that assists us in the search for food, and mental change emerges as a consequence. The major mental causation hypothesis: anxiety causes eating disorders, has been extensively tested and falsified. And the subsidiary hypothesis: anxiety and eating disorders are caused by the same genotype, generates inconsistent results because the phenotypes are not traits, but vary along dimensions. Challenging the mental causation hypothesis in 1972 already, Feighner et al. noted that anorexic patients are physically hyperactive and, hoarding for food they are rewarded for maintaining a low body weight (Feighner et al., 1972). In 1996, Feighner´s hypothesis was formalized, relating the patients´ behavioral phenotype to the brain mechanisms of reward and attention (Bergh and Södersten, 1996), and in 2002, the hypothesis was clinically verified by training patients how to eat normally, thus improving outcomes (Bergh et al., 2002). Sixteen years on, we verify Feighner´s hypothesis once more by showing that out of 174 patients admitted to our clinic in 2012, 37 were referred with a psychiatric diagnosis, which differed from the psychiatric diagnosis indicated by the Structured Clinical Interview for DSM–IV Axis I Disorders (SCID-I) in 20 of the 37 cases. Further on, there was significant disagreement between the outcome of the SCID-I interview and the patient´s subjective experience of a psychiatric problem in 110/174 of the cases. In addition, 358 anorexic patients treated to remission scored high on the Comprehensive Psychopathological Rating Scale, but an item response analysis indicated one underlying dimension, rather than the three dimensions the scale can dissociate in patients with psychiatric disorders. These results indicate that psychiatric diagnoses, which are reliable and valid in patients with psychiatric disorders, are less well suited for patients with anorexia. The results are in accord with the hypothesis of the present Research Topic, that eating disorders are not always caused by disturbed psychological processes, and support the alternative, clinically relevant hypothesis that the behavioral phenotype of the patients should be addressed directly.